Nowe media - nowe dziennikarsto - ? - Mielcarek, Małgorzata (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article shows the transformation of journalists’ and information’s functions, basing on the examples coming straight from the internet as it is the cause of all changes. Because of the new media, these functions are far more different today than 20 years ago. Traditional journalism is changing because of the Internet. At the same time, it is also coping with the new reality of presenting news. The question is: Can we call it the new journalism? Journamorfosis in Poland is definitely slower than in other countries. However, it is happening. There is higher control over journalists, even taking away their duties. The author proves that Polish journalism, thanks to the new media, finds itself in a different point than 20 years ago and it is still changing.